Development of starch/cellulose nanofiber bionanocomposite films containing thymol as active food packaging material - Othman, Siti Hajar; Nordin, Norhazirah; Kadir Basha, Roseliza; Abdul Rashid, Suraya (2023)
The main issue encountered in the food industry is the contamination and spoilage of food caused by microbes that result in food wastage and foodborne illness. Active food packaging is a new and innovative type of packaging that can help to solve this issue. Due to the consumer demands for environmentally friendly and sustainable packaging materials, the development of active food packaging material is now directed towards utilizing biopolymers and natural antimicrobial agents. Biopolymers such as starch are promising to be developed into food packaging material owing to their film-forming ability, biodegradability, and low cost. Hence, this work was directed towards exploiting starch for the production of active food packaging material that is environmentally friendly and sustainable. Cellulose nanofiber (CNF) which acts as a reinforcing compound was incorporated into the starch films, thus producing starch/CNF bionanocomposite films. Moreover, thymol, an antimicrobial agent was also added producing starch/CNF/thymol films. The films were produced using a solvent casting method and characterized in terms of mechanical, thermal, barrier, and antibacterial properties. The addition of CNF to the starch films was found to improve the mechanical, thermal, and barrier properties of the films. Meanwhile, the addition of thymol reduced the mechanical and barrier properties but increased the thermal stability of the films. The disc diffusion assay revealed clear inhibition zones of starch/CNF/thymol films against bacteria. A liquid culture analysis also confirmed the inhibitory effect of the films whereby there was a reduction in the number of bacteria in log CFU/mL. To demonstrate the application of the films, the films were applied in contact with meat slices and stored for 7 days. The meat samples in contact with the films containing thymol were less impacted by microbes than the films without thymol. In conclusion, this study will be advantageous to the agri-food and packaging industries, whereby the new environmentally friendly active food packaging material can be produced and applied to improve the shelf life of food products and has the potential to be commercialized, contributing to economic growth.